An Analysis of Simile in War Room Movie - Natanael, Yosua Timotius; Indriani, Gina; Nugraha, Muhammad Ridho Fajar; Handayani, Nurma Dhona (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2022)
The aim of this research is to analyze simile and its type in the movie “War Room” (2015) directed by Alex Kendrick. Similes are employed in a number of ways and serve a range of purposes, including movie. Therefore, this study applied qualitative research as the design and focused on analyzing simile, which is part of semantics study. A simile is a clear comparison, and it frequently uses comparative terms like or as. The type of similes is categorized by Dancygier & Sweetser (2014) into narrow-scope and wider-scope similes. As the result of the research, there were 20 similes found in the movie, such as 4 similes using “as” and 16 similes using ‘like’ as the comparison word. Moreover, there were 11 narrow-scope similes and 9 wider-scope similes apparent in the movie’s narration and conversation.